Analysis of the dry whirl and dry whip response in a vertical active magnetic bearing drop test rig. (14th April 2023) - Li, Zilin; Yao, Jiakang; Ma, Long; Yang, Guojun; Lyu, Mindong; Wang, Yuming; Wang, Zixi
Highlights: Simulation ability of dynamic response to the complete AMB-rotor drop process;. Theoretical analysis of dry whirl and dry whip of a vertical rotor;. Simulation model and test rig together verify the theoretical validity;. Parametric study of the factors influencing the natural whirl speed. Abstract: A horizontal rotor is usually the research subject of rotor drop failure in active magnetic bearing (AMB) test rigs. However, research shows, that a vertical rotor drop failure is not sufficiently understood at present. The experiments in other research studies show that the vertical rotor dynamic response is not simple whirl behavior after dropping on the touchdown bearing (TDB), which concludes dry whirl and dry whip processes, where the former is synchronous forward whirl, and the latter is subsynchronous forward whirl. To predict the dynamic response of a vertical rotor drop failure, theoretical research based on a rotor-TDB model system is developed in this paper, and the effectiveness of this model is validated by an AMB-TDB rotor experiment. The conclusion is that the natural whirl speed and the resulting critical speed clearly distinguish two states of forward whirl motion. When the rotation speed is less than the critical speed, the rotor is in a dry whirl state; otherwise, it behaves as in a dry whip. The rotor unbalance is introduced in the model, which explains the change in the whirl speed. Moreover, the influencing factors on the natural whirl speed are analyzed in depth. The result shows that parameters of the TDB, such as the friction coefficient and protective clearance, and the rotor unbalance have significant effects.